A study on optimum insulation thickness of building walls in hot summer and warm winter zone in China - Chengcheng Xu; Suola Shao; Wenjian Wei; Yanluan Qin; Nan Li (Scientific Reports)
Abstract As the proportion of building energy consumption gradually increases, adding insulation materials to the existing building envelope has become an important method to improve building thermal performance. Currently, most research on the optimum thickness of insulation layers is calculated from the perspective of heat transfer. However, in humid and hot areas, the influence of humidity and solar radiation should not be ignored. Therefore, this study used the coupled heat and moisture transfer model to calculate the yearly cooling and heating transmission loads. Three kinds of materials: expanded polystyrene, polyurethane and extruded polystyrene were compared in thickness ranging from 10 to 90 mm. The P1-P2 economic model consisting of lifecycle energy P1 and lifecycle expenditure ratio P2 was used to calculate the optimum thickness, payback periods and energy savings. The results show that, the optimum thicknesses for expanded polystyrene, polyurethane, and extruded polystyrene are 66.8 to 74.5 mm, 38.3 to 40.2 mm, and 46.3 to 49.5 mm, respectively. The required payback periods are 5.57 to 5.72 years, 6.86 to 7.47 years, and 6.32 to 6.74 years, respectively. Expanded polystyrene is the most economical thermal insulation materials because of its lowest lifecycle total cost, the shortest payback period and the most energy savings. This study is helpful for obtaining more accurate optimum thickness of insulation layer in hot and humid areas, and guiding the renovation of existing buildings.